An enhanced buffer management scheme for fast handover protocol - Wei-Min Yao; Yaw-Chung Chen (24th International Conference on Distributed Computing Systems Workshops (ICDCS 2004 Workshops), 2004)
The integration of IEEE 802.11 wireless LAN and mobile IP technologies offers an affordable and high bandwidth solution for host mobility. When applying the hierarchical mobile IP for fast handover, the performance bottleneck on mobile IP and potential disconnection during handoff period can be greatly improved. However, the fast handover protocol suffers several problems such as scalability and QoS support for lacking a buffer management mechanism. We propose an enhanced buffer management scheme for fast handover. By means of the proposed scheme, we are able to improve the buffer utilization on routers as well as to support QoS services during a handoff process. Using the ns-2 simulator, we have demonstrated the significance and effectiveness of our proposed scheme.